FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGUNGKAPAN SUSTAINABILITY REPORT - Natalia, Orien; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to obtain empirical evidences about some factors which influence the level of Sustainability Report disclosure. In this research the financial performance is proxy by the Sustainability Report (SR). The research samples have been selected by using purposive sampling method. The data is the documentary data and the source of data has been obtained from the official website i.e. www.idx.co.id, the internal web of the company and the STIESIA Surabaya Invesment Galery of Indonesia Stock Exchange. The data analysis technique has been done by using multiple linear regressions. By using the Goodness of Fit test, it can be stated that profitability, liquidity, leverage, firm size, corporate activity, audit committee, and board of directors are used to explain the variable of Sustainability Report (SR). Moreover, the result of the t test shows that Audit comittee has positive influence to the level of Sustainability Report disclosure and Leverage has negative influence to the level of Sustainability Report disclosure whereas profitability, liquidity, firm size, corporate activity, and board of director do not have any influence to the level of Sustainability Report disclosure.Keywords: Profitability, liquidity, leverage, firm size, corporate activity, audit committee, board of directors, sustainability Report